Determination of Cu, Ni and Pb in Aqueous Medium by FAAS after Pre-Concentration on 2-Aminothiazole Modified Silica Gel - De Alcântara, Ilton Luiz [UNESP]; Dos Santos Roldan, Paulo [UNESP]; Margionte, Maurício A. L. [UNESP]; Castro, Gustavo R. [UNESP]; Padilha, Cilene C. F. [UNESP]; De Oliveira Florentino, Ariovaldo [UNESP]; De Magalhães Padilha, Pedro [UNESP] (FapUNIFESP (SciELO), 2004)
This work describes the synthesis and characterization of 2-aminothiazole modified silica gel (SiAT), and the results of a study of the adsorption and pre-concentration (in batch and using a flow-injection system coupled to an absorption atomic spectrometer) of Cu(II), Ni(II) and Pb(II) in aqueous medium. The adsorption capacities for each metal ions in mmol g -1 were: Cu(II)= 1.18, Ni(II)= 1.15 and Pb(II)= 1.10. The results obtained in the flow experiments showed a recovery of practically 100% of the metal ions adsorbed in a mini-column packed with 100 mg of SiAT, using 100 μL of 2.0 mol L -1 HCl solution as eluent. The sorption-desorption of the metal ions made possible the application of a flow-injection system for the pre-concentration and quantification by FAAS of metal ions at trace level in natural water samples digested and not digest by an oxidizing UV photolysis.
Keywords: 2-aminothiazole modified silica gel; FAAS; Pre-concentration; Water samples; 2 aminothiazole derivative; copper; hydrochloric acid; lead; metal ion; nickel; silica gel; adsorption; aqueous solution; atomic adsorption spectrometer; batch process; chemical analysis; chemical modification; concentration (parameters); desorption; flow injection analysis; oxidation; photolysis; quantitative analysis; spectrometer; synthesis; ultraviolet radiation; water sampling